(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In order to understand the effect of moisture content on the dynamic characteristics of rubber-sand particles (Rubber-Soil Mixture, RSM), a dynamic triaxial test was carried out. Before the test, the rubber particles and sand were mixed according to the rubber volume ratio of 0%, 25%, 30%, 40%, 50%, 75%, and 100%, and the water content was 0%, 5%, and 10%. The confining pressure control of the triaxial test is 50, 100, 200, a total of 63 groups of tests. In the test, the effects of dynamic triaxial confining pressure, rubber particle content and moisture content on RSM were investigated respectively. The test results show that: (1) under the same rubber particle content, the dynamic shear modulus of the RSM sample increases with the increase of the confining pressure; (2) with the increase of the rubber particle content, the dynamic shear modulus of the RSM sample increases. The shear modulus decreased significantly; (3) The change of water content did not cause significant changes in the dynamic shear modulus of RSM samples. The test results can be used as a reference for the engineering application of RSM seismic isolation technology in the future.